OPENAI IN EDUCATION: STUDENT’S EXPERIENCES IN UTILIZING ARTIFICIAL INTELLIGENCE FOR ACADEMIC PURPOSES WITHIN ASTANA REGION - Suleimanova, Alua (Nazarbayev University School of Sciences and Humanities, 2024)
This study investigates the undergraduate student's experiences in utilizing Artificial Intelligence (AI) for academic and daily purposes within the Astana region. The investigation employs the theoretical framework of cultural capital proposed by Pierre Bourdieu to analyze and understand complex dynamics. The research has a qualitative design, including eight individual interviews with undergraduate students from four different universities in Astana city. Data analysis is based on an inductive thematic approach to extract findings and patterns from the study. The results indicate that students' interactions with AI vary depending on individual cultural capital factors, such as the language of instruction at university, language proficiency, social network, nature of assignments, and presence of AI-detection software systems. Additionally, institutional policies also play a significant role in shaping students' experiences with AI within educational settings
Keywords: Type of access: Open; Astana; Artificial Intelligence; Education; OpenAI; Education Technology; Undergraduate Students